Phase retrieval in inverse ghost diffraction using Sagnac interferometer - Gautam A.; Chandra S.; Singh R.K. (My University, 2025)
Ghost diffraction (GD) involves the use of non-local spatial correlations to image objects with light, which has not interacted with them. Here, we propose and experimentally demonstrate a new technique for first-order correlation measurement and retrieval of two-dimensional phase objects in the GD from inversion of the experimentally measured two-point complex correlation function in a first order interferometer. The GD scheme is experimentally implemented by a specially designed experimental setup wherein one of the orthogonal polarization components of the transversely polarized light interacts with the object and the other polarization component of the light remains intact and directly reaches the detector. The Fourier spectrum of the object is encoded into the two-point spatial correlation of these two orthogonal polarization components which is experimentally detected in an interferometer with a radial shearing in the Sagnac geometry. We experimentally demonstrated imaging of spatially varying phase objects and results are presented for three different cases. © 2024 IOP Publishing Ltd.